1996
DOI: 10.1046/j.1365-2125.1996.37912.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the function of cytochrome P450

Abstract: 1The role that P450 plays in the metabolism of drugs and other chemicals is often pivotal in determining the duration and magnitude of their biological effects, so that it is important to identify the specific forms of the enzyme involved. 2The similarity between different forms of P450 is such that polyclonal antibodies raised by conventional means, even against a homogeneous preparation of the enzyme will often react with several different P450s. 3Whilst monoclonal antibodies are often more specific, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…There is considerable overlap between CYP3A enzymes in substrate-specificity [ 32 ]. Many previous studies have argued that CYP3A4 has the most significant role of all CYP3A enzymes in therapeutic drug metabolism [ 33 ]. However, CYP3A5 is one of the most pharmacologically active drug metabolizing enzymes in Africa [ 29 ].…”
Section: The Clinical Significance Of the Cytochrome P450 Super-familmentioning
confidence: 99%
“…There is considerable overlap between CYP3A enzymes in substrate-specificity [ 32 ]. Many previous studies have argued that CYP3A4 has the most significant role of all CYP3A enzymes in therapeutic drug metabolism [ 33 ]. However, CYP3A5 is one of the most pharmacologically active drug metabolizing enzymes in Africa [ 29 ].…”
Section: The Clinical Significance Of the Cytochrome P450 Super-familmentioning
confidence: 99%
“…Another study showed that only 3% of human liver had detectable CYP3A5 by immunoblotting (Boobis et al, 1996). These findings suggested that CYP3A5 polymorphism might play an important role in functional regulation.…”
mentioning
confidence: 95%
“…7 The quantification methods that are most widely used today are immunological techniques such as ELISA and Western blotting 8 which rely on the availability of specific antibodies. Although tremendous efforts have been made to develop isoform-specific monoclonal 9 or anti-peptide antibodies, 10 the simultaneous and comparative quantification of CYP enzymes is still a very difficult task because of their high similarities both in sequence and in molecular weight. For example, recent data on the relative expression levels of CYP3A4 and CYP3A5 have remained controversial.…”
Section: Introductionmentioning
confidence: 99%